analysis of the influence of emotional development on early childhood personality development - hamzia marie (incrementapedia, 2021)
Abstract Child’s emotional development is very influential on the development of child’s personality, where children have different emotional/temperament: children with easy temperament, children with difficult temperament, children with slow temperament. In this research, the researcher wants to analyze phenotypic in the scope of psychological character, that is the child’s personality, which personality has the effect of the emotional development of the child. The methodology used in this preparation uses a qualitative method with a literature review approach. The emotional experience of an individual is increasingly widespread with his experience in experience self-conscious emotions such as pride, shame, and guilt. There are several factors that influence the emotional development of children, so these emotions are very influential on their personality, namely: parenting, wrong behavior in children, individual relationships with siblings and birth order of an individual, individual relationships with peers, play, and television.